Proposal for the implementation of a customer centric management system based on artificial intelligence - Cervantes Gutiérrez, Sebastián Camilo (2022)
The main objective of this explanatory research with a quantitative approach is to support the implementation and development of a “customer-centric” management system based on artificial intelligence (machine learning) as a recovery measure against the current context resulting from the global pandemic. In addition, through the approach of the necessary technological tools and the understanding of the target population, the aim is to redesign and automate the service process of the restaurants to achieve an effective optimization of time.